Patients with Hypertensive Nephropathy and Chronic Kidney Disease Might Not Benefit from Strict Blood Pressure Control - Simone Vettoretti; Lara Caldiroli; Francesca Zanoni; Valeria Azzini; Anna Villarini; Roberto Meazza; Piergiorgio Messa (Karger Publishers, 2018)
Background/Aims: In patients with chronic kidney disease (CKD) strict blood pressure (BP) control is reno-protective. However, renal benefits from BP control might depend also on the etiology of CKD. We investigated if maintenance of BP at target is equally effective in subjects with hypertensive nephropathy (HN+) and in those with other nephropathies (HN-). Methods: We evaluated 148 patients with CKD (stages 3-5) in two visits at least 12 months apart. BP was measured both as office BP and 24h ambulatory blood pressure (ABP). Glomerular filtration rate (eGFR) was estimated with CKD-EPI formula. The slope of eGFR variation (ΔeGFR) was calculated as: (eGFR1-eGFR0)/months of follow up. Results: Cohort characteristics were: HN-(n=82) and HN+ (n=66), age (71±9 vs 74±9 years; p=0.09); prevalence of diabetes (57 vs 43%; p=0.19); average follow up (19±7 vs 21±9 months; p=0.3). HN- and HN+ did not differ regarding both baseline eGFR (34±18 vs 35±14 ml/min; p=0.97) and ΔeGFR (0.00±0.53 vs -0.06±0.35 ml/min/month, p=0.52). The proportion of patients with BP at target at both visits was similar in HN- and HN+ (office BP: HN- 18% and HN+ 27%; p=0.21; ABP: HN- 42% and HN+ 43; p=0.96). In patients with office BP at target at both visits HN- showed a significant improvement of ΔeGFR respect to HN+ (HN-: 0.240 ± 0.395 and HN+: -0.140±0.313 ml/min/ month; p=0.026). In patients with office BP not at target HN- and HN+ did not show any difference in ΔeGFR (HN- 0.00±0.47; HN+ -0.030±0.420 ml/min/month; p=0.66). ABP was not associated with differences in ΔeGFR either if it was at target (HN- 0.104±0.383 and HN+ 0.00±0.476 ml/min/month; p=0.42) or not (HN- -0.057±0.503 and HN+ -0.092±0.325 ml/ min/month; p=0.87). Conclusion: In patients with CKD and HN+ maintenance of BP targets recommended by current guidelines is less reno-protective than it is in HN-.